HAEMATOLOGICAL PARAMETERS AND OUTCOME IN HOSPITALIZED PATIENTS WITH COVID-19: A DEVELOPING COUNTRY EXPERIENCE - Iftikhar, Raheel; Kamran, Sultan Mehmood; Mirza, Zill-e-Humayun; Naseem, Arshad; Shah, Syed Asif Ali; Riaz, Sidra; Fazal, Imran; Alamgir, Wasim; Saeed, Farrukh; Saleem, Salman; Ali, Rao Saad; Chaudhry, Qamar (Journal of Ayub Medical College Abbottabad, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a multisystem disorder and haematological abnormalities are frequently documented in affected patients. Methods: This retrospective study included 549 patients hospitalized with COVID-19 from 1st June to 15th July 2020 at Pak Emirates hospital, Rawalpindi Pakistan. p<0.05 was considered statistically significant. Results: Median age was 60 years (range 12-94 years), males 442 (80.5%) and females 107 (19.5%). There was no patient with mild illness, 181 (32.9%) had moderate, 158 (28.7%) severe and 210 (38.2%) patients had critical disease. Patients with severe and critical disease had lower absolute lymphocyte count (ALC) and platelets (p<0.001 for both) while higher white blood cell count (WBC), neutrophil lymphocyte ratio (NLR), C-reactive protein (CRP), interleukin-6 (IL-6) and lactate dehydrogenase levels (LDH) levels (all p<0.001). Overall survival of study cohort was 83.2%(n=457). Median haemoglobin and platelet count were significantly lower (p<0.001) while WBC, ANC, NLR, prothrombin time (PT), activated partial thromboplastin time (APTT), ferritin, IL-6, LDH were significantly higher (p<0.001) for patients who died. On multivariate logistic regression analysis WBC count>10x109/l (odds ratio [OR] 2.19 [95% CI 1.3-4.2] p=0.01), NLR>9 (OR 3.4 [95% CI 0.87-6.8], p<0.001), platelets<150x109/l (OR 3.9 [95% CI 1.4-9.8] p<0.001), CRP >100; (OR 4.1[95% CI 0.78-10.9] p<0.001) and ferritin >1000 (OR 5.3 [95% CI 1.9-13.5], p<0.001) were associated with increased risk of death in patients with COVID-19. Conclusion: Monitoring of haematological, coagulation and inflammatory parameters provide reliable, convenient, rapid and cost-effective method for predicting disease severity, complications and prognosis of COVID-19 patients.